(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
The rapid digitalization of society has transformed occupational therapy practice, introducing both opportunities and challenges. As occupational therapists increasingly rely on electronic documentation, telehealth, and assistive technologies, cybersecurity is emerging as a critical concern. This position paper argues that occupational therapy is a vital domain for the integration of cybersecurity education, emphasizing the need to safeguard sensitive patient information, enhance digital literacy, and address the unique vulnerabilities faced by occupational therapy clients. The paper outlines the key intersections of occupational therapy and cybersecurity education, highlighting the impact of cyber threats on healthcare, the importance of digital literacy, and the role of occupational therapy in educating and protecting vulnerable populations. Recommendations are provided for integrating cybersecurity education into occupational therapy curricula and fieldwork education to better prepare practitioners for the evolving digital landscape. By integrating cyber safety principles into occupational therapy education, the field can fulfill its mission of enhancing individuals’ participation in meaningful activities by equipping practitioners with the skills necessary to protect patient data, manage evolving digital risks, and ensure safe, effective care in a technology-driven world.